Prediction of protein–protein interactions between fungus (Magnaporthe grisea) and rice (Oryza sativa L.). (11th October 2017) - Ma, Shiwei; Song, Qi; Tao, Huan; Harrison, Andrew; Wang, Shaobo; Liu, Wei; Lin, Shoukai; Zhang, Ziding; Ai, Yufang; He, Huaqin
Abstract: Rice blast disease caused by the fungus Magnaporthe grisea ( M. grisea ) is one of the most serious diseases for the cultivated rice Oryza sativa ( O. sativa ). A key factor causing rice blast disease and defense might be protein–protein interactions (PPIs) between rice and fungus. In this research, we have developed a computational pipeline to predict PPIs between blast fungus and rice. After cross-prediction by interolog-based and domain-based method, we achieved 532 potential PPIs between 27 fungus proteins and 236 rice proteins. Accuracy of jackknife test, 10-fold cross-validation test and independent test for these PPIs were 90.43, 93.85 and 84.67%, respectively, by using support vector machine classification method. Meanwhile, the pathogenic genes of blast fungus were enriched in the predicted PPIs network when compared with 1000 random interaction networks. The rice regulatory network was downloaded and divided into 228 subnetworks with over six nodes, and the top seven subnetworks affected by blast fungus through PPIs were investigated. The results indicated that 34 upregulated and 12 downregulated master regulators in rice interacting with the fungus proteins in response to the infection of blast fungus. The common master regulators in rice in response to the infection of M. grisea, Xanthomonas oryzae pv.oryzae and rice stripe virus were analyzed. The ubiquitin proteasome pathway was the common pathway in rice regulated by these three pathogens, while apoptosis signaling pathway was induced by fungus and bacteria. In summary, the results in this article provide insight into the process of blast fungus infection.